Skrining Fitokimia Ekstrak Etanol Biji Buah Tarap (Artocarpus odoratissimus) - Virda Putri Lestari; Sari Wijayanti; Faizal Mustamin (Journal Borneo, 2024)
Tarap fruit (Artocarpus odoratissimus), also known as "terap", is a type of fruit that grows in various tropical regions in Southeast Asia. because almost every part of the fruit has pharmacological properties, it is often used as an ingredient in traditional medicine. The plant has been part of many different cultures for a long time, used as a food source, and is widely used to help improve health. This study aims to conduct phytochemical screening on tarap fruit seed extract to identify the secondary metabolite compounds contained in it with a focus on compounds such as polyphenols, alkaloids, tannins, saponins, steroids, and terpenoids. This study uses a qualitative experimental method to analyze phytochemistry by color test using various reagents from tarap fruit seed extract, to identify secondary metabolite compounds in the plant. Tarap fruit seed samples were obtained from local fruit sellers in Tarakan. Extraction of tarap fruit seeds was carried out using 96% ethanol with maceration technique, then examined the content of polyphenols, alkaloids, tannins, saponins, steroids and terpenoids. The results showed the presence of several secondary metabolites in tarap fruit seed extract, proving the content of polyphenols, alkaloids, saponins, and terpenoids, while tannins and steroids could not be detected. The conclusion is that the ethanol extract of tarap fruit seeds (Artocarpus odoratissimus) contains polyphenols, alkaloids, saponins, and terpenoids.